Simulation of heat transfer in combustion chamber waterwall tubes of supercritical steam boilers - Grądziel Sławomir (Chemical and Process Engineering, 2016)
The paper presents the results of numerical computations performed for the furnace chamber waterwalls of a supercritical boiler with a steam output of 2400 × 103 kg/h. A model of distributed parameters is proposed for the waterwall operation simulation. It is based on the solution of equations describing the mass, momentum and energy conservation laws. The aim of the calculations was to determine the distribution of enthalpy, mass flow and fluid pressure in tubes. The balance equations can be brought to a form where on the left-hand side space derivatives, and on the right-hand side – time derivatives are obtained. The time derivatives on the right-hand side were replaced with backward difference quotients. This system of ordinary differential equations was solved using the Runge-Kutta method. The calculation also takes account of the variable thermal load of the chamber along its height. This thermal load distribution is known from the calculations of the heat exchange in the combustion chamber. The calculations were carried out with the zone method.